Examining Response Time and Accuracy in Jumbled Procedure Text Tasks Through Speed–Accuracy Trade-Off Theory - Mayla Fayza; Rizka Hayati (IKIP Siliwangi, 2026)
Response time is often overlooked in EFL reading assessment, despite its potential to reveal students’ cognitive processing. This research examines seventh-grade students’ response time and accuracy in completing a jumbled procedure text task based on the Speed–Accuracy Trade-Off (SAT) theory. Using a quantitative descriptive design, the research involved students from a junior high school in Indonesia. Data were collected through a digital task administered via Wordwall, measuring both accuracy and response time. The findings indicate considerable variation in students’ performance, suggesting that learners employ different response strategies when completing the task. While a majority of students demonstrated patterns consistent with the classic speed–accuracy trade-off, a substantial proportion showed non-trade-off patterns, indicating that speed and accuracy do not always operate inversely in classroom-based language tasks. Furthermore, the relationship between response time and accuracy was found to be weak, implying that accuracy alone cannot adequately explain students’ response behavior. These results highlight the importance of integrating response time as a complementary indicator in reading assessment. By considering both speed and accuracy, teachers can gain a more comprehensive understanding of students’ cognitive processing and design more effective instructional strategies.